Evaluating the impacts of traditional biomass energy use on agricultural production in Sichuan, China - Qiu Chen; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2016)
As crop straw and firewood are generated as by-products of food production systems, they are perceived to be sustainable energy sources that do not threaten food security by Chinese government for a long time. However, the time spent on collecting straw and firewood may create a burden on rural household, as it could reduce the available labor inputs for agricultural production, which in turn, possibly brings negative impact on food security. Building on an integrated agriculture-energy production system, a Symmetric Normalized Quadratic (SNQ) multi-output profit function (which includes labor allocations as quasi-fixed factors) is estimated to investigate the impacts of traditional biomass energy use on agricultural production in this paper. The negative signs of the calculated cross-price elasticities of supply (agricultural products and biomass energy) confirm that the relationship between biomass collection and agricultural production is competition. Moreover, the cross-price elasticities of biomass collection with respect to inputs are positive, implying that indirect link between biomass collection and agricultural production perhaps lies in household consumption decisions. The important implication of this study is that potential policy interventions for developing biomass energy in rural China could aim at enhancing food security by improving household motivation of engaging in agricultural production and slowing down the competition between biomass collection and agricultural production. It is suggested that government should attach more importance to simultaneously promote the prices of agricultural products and control the prices of intermediate inputs.
Keywords: O13; Q01; Q12; Q41; 330; biomass collection; agricultural production; labor allocation; China